Construction of full solar-spectrum available S-scheme heterojunction for boosted photothermal-assisted photocatalytic H2 production - Shi, Yuxing; Li, Lingling; Xu, Zheng; Guo, Feng; Shi, Weilong (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •Co3O4 as a heat source in composite system can generate heat by absorbing Vis-NIR light.•High-frequency photons are converted into heat to accelerate interfacial charge transfer.•S-scheme retains carriers with high redox potentials converted from low-frequency photons. The development of photocatalysts that maximize the use of solar spectra for photocatalysis for obtaining more efficient photocatalysts is urgently needed. Herein, the core–shell Co3O4@ZnIn2S4 S-scheme heterojunction was synthesized for achieving high-efficient photothermal-assisted photocatalytic hydrogen (H2) performance under full solar-spectrum irradiation. Notably, photocatalytic H2 production tests indicate that the as-prepared optimal Co3O4@ZnIn2S4 sample (CO@ZIS-20) exhibits impressive H2 production rates of about 18.9 and 9.8 mmol h−1 g−1 under AM 1.5G and real sunlight irradiation, respectively. The effect of the reaction solution temperature induced by the photothermal effect on the photocatalytic activity in solid–liquid reactions was also investigated. Furthermore, the results of the characterization analysis revealed that high-frequency photons dominate photocatalytic reactions while low-frequency photons are converted into heat to improve photocatalytic reactions. This study provides effective design ideas of developing high-activity photothermal-assisted photocatalysts for realizing solar energy conversion.